Kontribusi Pendekatan Konstruktivisme dalam Meningkatkan Partisipasi Siswa dalam Pembelajaran Pendidikan Agama Katolik di SMA Negeri 1 Lewolema - Margaretha Ema Tukan; Hermania Bhoki; Krisantus Minggu Kwen (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The purpose of this study was to analyze the contribution of the construktivist approach in increasing student participation in Catholic Religious Education learning at SMA Negeri 1 Lewolema. The research method used was qualitative with a descriptive approach. The results of this study are that Catholic Religious Education teacgers have implemented a construtivist approach by trying to link learning materials with the initial knowledge that students already have. However, the implementation of this approach encountered obstacles because some students had inadequate initial knowledge. Student participation in learning which includes five indicators, namely: expressing opinions, giving responses, doing assignments, making conclusions, and presenting has not been realized properly. This study concludes that the application of the constructivist approach in Catholic Religious Educations learning has not been able to optimally increase student participation, which is caused by severral internal factors from students.